Thyroid function disorders - Stojković, Mirjana (Archives of Pharmacy, 2022)
Thyroid function disorders are the most common endocrine disorders in humans. They are frequently diagnosed, with prevalence varying between 2 and 6%, and a female to male ratio of up to 10:1. Disorders of thyroid function in the narrower sense are presented by its hyperactivity or underactivity, although there are conditions that lead to an increased concentration of thyroid hormones, without its increased activity. In iodine-sufficient regions, the most common cause of hyperthyroidism, as well as hypothyroidism, is an autoimmune disease of the thyroid. For hyperthyroidism, it is Graves’ disease, with typical symptoms and signs of hypermetabolism. The diagnosis of hyperthyroidism is based on suppressed TSH and elevated fT4 (free, and in the differential diagnosis, elevated TSH-receptor-antibodies are crucial for Graves’ disease. Management of Graves’ disease relies on three equally potent approaches: medical therapy, ablative treatments with 131I-radiotherapy-RAI, and thyroidectomy. Hashimoto’s thyroiditis is the most common cause of hypothyroidism in iodine-sufficient regions. Symptoms and signs of hypothyroidism are non-specific and correspond to the symptoms and signs of hypometabolism. The diagnosis is made based on elevated TSH ​​with decreased fT4. Thyroxine-peroxidase-antibodies and thyroglobuline-antibodies are important in differential diagnosis. Sometimes elevated TRAb is found in Hashimoto’s thyroiditis. The treatment of hypothyroidism is levothyroxine replacement therapy.